Oil and gas industry hydrotechnical structures design - Mammadyarova, Taravat; Pashchenko, O. A. (НТУ ДП, 2022)
The gradual depletion of oil and gas reserves on land and the aggravation of the global energy crisis necessitated the ever wider development of the oil and gas resources of the seabed, which contains almost three times more oil and gas than on land. Offshore oil and gas production projects will be actively developed in the coming years, given the clear global need for large volumes of fossil fuels, as evidenced by the ongoing energy crisis in Europe and shortages in the markets.
Keywords: гидротехническое сооружение; нефтегазовая отрасль